(untitled) (Revista de Ciências Agroveterinárias, 2006)
This study aimed to evaluate the association between the groups of soil fauna and the soil chemical attributes in systems of no-tillage and conventional tillage. The experiment was carried out from August of 2004 to January of 2005, in the Agronomic Institute of Campinas (IAC), Campinas, SP. Four representative areas of the region with 0.3 ha each were selected: 1) no-tillage established since 1986; 2) no-tillage established since 1999; 3) conventional tillage since 1999 and 4) conventional tillage since 2000. The capture of the organisms was performed with ten pit fall traps installed on each area. The soil samples to assess soil chemical attributes were collected at the depth of 0-10 cm. After counting each group of soil fauna captured in each trap (abundance), the Shannon’s diversity index (H), Simpson’s dominance index (Is) and Pielou’s uniformity index (e) were determined. The data were submitted to the multivariate grouping analysis and together with the soil chemical attributes submitted to the canonical correspondence analysis (CCA). Cluster analysis demonstrated similarity between the two no-tillage systems (T1 and T2), forming a separate group from the two conventional planting systems (T3 and T4). The CCA enabled the separation of four agricultural systems, indicating the groups of soil fauna and chemical attributes mostly associated to each area. The long term-established no-tillage system presented a greater activity and diversity of the soil fauna.